Can the Healthcare Assistant in General Practice provide Preventative Support for Older People to Reduce Risk of Falls? - Hodgins, Diana; Newby, Jack (British Journal of Healthcare and Medical Research, 2023)
In 2014, 2,734 people over 65 across the four London boroughs were predicted to have been admitted to a hospital because of falls. This figure is predicted to rise further to 3,766 by 2030. The number of falls can be reduced by up to 30% through development of a multi-agency falls pathway focussing on early identification and prevention, and multi-factorial assessment and intervention for people at high risk of falling (1). The role of the health-care assistant (HCA) has developed rapidly in general practice and HCAs can make an increasingly useful contribution to the skill mix in general practice. The project aimed to evaluate; the suitability of HCAs delivering GaitSmart assessments in the GP clinical pathway, GaitSmart protocol for detecting gait deficiency and improving gait and patient reported outcomes (Gait Speed, GaitSmart Score, Falls Efficacy Scale Questionnaire (FES-I) and Edmonton Frailty Score (EFS). The programme produced positive patient outcomes, thus reducing the burden on physiotherapists. Participants who completed the three-session GaitSmart intervention programme showed an average improvement in their gait characteristics